PENGARUH KEBERAGAMAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Top 50 Perusahaan dengan Kapitalisasi Pasar Terbesar yang Terdaftar di BEI tahun 2016-2018) - Asma Muthiah Syahidah; Dwi Ratmono (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of board of commissioner diversity on corporate social responsibility disclosure. The dependent variable that used in this study is corporate social responsibility disclosure. The proportion of independent commissioner, tenure of the board of commissioners, female commissioner, and the proportion of former director in the board of commissioners are used as independent variables. The sample in this study consists of 84 companies that listed on Indonesia Stock Exchange in the period 2016-2018. This study used secondary data and selected by using purposive sampling method. The technique of analysis used for examining the hypothesis is multiple regression analysis panel data. The empirical results of this study show that female commissioner has positive influence on corporate social responsibility disclosure. While the proportion of independent commissioner, tenure of the board of commissioners, and the proportion of former director in the board of commissioners do not have influence on corporate social responsibility disclosure.